Penerapan Keselamatan Kerja dan Kesehatan Kerja Melalui Manajemen Sekuriti Terhadap Produkivitas Pada PT. Epson - Vina Damayanti; Edy Soesanto; Indra Samuel; Harfanly Bramley (Jurnal Ilmiah Wahana Pendidikan, 2023)
Security is a condition in which humans or objects feel protected from threatening or disturbing dangers, which in turn will lead to feelings of calm and comfort. Security can be obtained in several ways, one of which is by using and implementing technology. The application of security technology has now developed very rapidly, ranging from conventional to high-tech methods. In terms of security, all methods require a key as validation. This study uses a qualitative approach, this approach is characterized by an in-depth search for information from several sources. Data is collected then processed and analyzed and decisions are made. To collect complete information. This study aims to determine the security management system as well as occupational safety and health and work productivity at PT. Epson Indonesia, to find out the obstacles in implementing security and occupational safety and health at PT. Epson Indonesia and to find out the existing productivity at PT. Epson Indonesia.